Nest site selection in the European wool-carder bee, Anthidium manicatum, with methods for an emerging model species - Payne, Ansel; Schildroth, Dustin A.; Starks, Philip T. (Apidologie, 2011)
For many organisms, choosing an appropriate nest site is a critical component of reproductive fitness. Here we examine nest site selection in the solitary, resource defense polygynous bee, Anthidium manicatum . Using a wood-framed screen enclosure outfitted with food sources, nesting materials, and bamboo trap nests, we show that female bees prefer to initiate nests in sites located high above the ground. We also show that nest sites located at higher levels are less likely to contain spiderwebs, suggesting an adaptive explanation for nest site height preferences. We report size differences between this study’s source populations in Boston, Massachusetts and Brooklyn, New York; male bees collected in Boston have smaller mean head widths than males collected in Brooklyn. Finally, we argue that methods for studying captive populations of A. manicatum hold great promise for research into sexual selection, alternative phenotypes, recognition systems, and the evolution of nesting behavior.